Penggunaan Media Pembelajaran Spin Wheel Pada Materi Kepahlawanan Terhadap Hasil Belajar Kelas V SD - Dwi Putri, Anggi; Shinta Aulia Annisa; Karima Noor Malikatus Sa’adah; Zidan Fakihani; Budi Nur Ismail (Universitas Palangka Raya, 2023)
The goal to be achieved is to find out the use of spin wheel learning media on heroism material on class learning outcomes. This research is class action research (action research). This research was conducted in the form of cycles, each cycle consisting of several components, namely the stages of preparation, planning, implementation of action, observation and monitoring, reflection, evaluation and revision and conclusion of the results. The data validation process is carried out by asking for an assessment of experts and practitioners regarding the content and outline of the written test which is used as a data collection tool, so that the tool is used to measure student abilities. The use of the spin wheel learning model is proven to improve student learning outcomes. The learning process on the subject matter of heroism from the aspects of teachers and students can be achieved because from cycle to cycle there is reflection and improvement through good collaboration between researchers and observers. This result can be achieved because of this cooperation in designing, implementing, observing, and reflecting on cycles for two cycles. Improving mathematics learning outcomes through the spin wheel learning model in heroism material can be achieved.